The perceived characteristics of 'Knowledgeable' by UK MOD procurement function staff - Allen, Robby A.; Renfrey, Simon (IEOM Society, 2017)
A neglected aspect of the nature of expertise and knowledge is how personnel in public procurement are perceived. The purpose of this paper is to examine the characteristics of procurement staff who are perceived to be knowledgeable and those who are not. Fifty-eight UK Ministry of Defence procurement function staff completed an online survey. The study shows that how procurement personnel are regarded by colleagues is inclined towards ascribed attributes and this paper presents a delineation of those attributes to allow for greater understanding. An awareness of the perceptions of others has practical importance for procurement personnel and managers as it allows for the better understanding of how they are perceived and in doing so empowers them to build on strengths and identify areas for improvement. The study’s originality lies in the provision of an important insight into how staff within a complex and usually difficult to access public sector procurement environment are perceived by their colleagues.
Keywords: Perception; Expert; Knowledge; Procurement; Defence